2018
DOI: 10.1111/dom.13350
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral cannabinoid 1 receptor blockade mitigates adipose tissue inflammation via NLRP3 inflammasome in mouse models of obesity

Abstract: These results suggest that peripheral CB1R blockade improves obesity-induced insulin resistance by suppressing adipose tissue inflammation via the NLRP3 inflammasome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
(72 reference statements)
3
29
0
Order By: Relevance
“…Monocyte chemotactic protein 1 secretion was not affected by the knockdown of IRF5 (25). Similar to the previous reports (25,33), our results also showed that and the CB1Rinduced expression of Mcp1, Nlrp3, and Il1b in macrophages was regulated by the p38 MAPK-dependent pathways. In addition to affecting the expression levels of Nlrp3 and Il1b, it is likely that CB1R can directly cause NLRP3 inflammasome activation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Monocyte chemotactic protein 1 secretion was not affected by the knockdown of IRF5 (25). Similar to the previous reports (25,33), our results also showed that and the CB1Rinduced expression of Mcp1, Nlrp3, and Il1b in macrophages was regulated by the p38 MAPK-dependent pathways. In addition to affecting the expression levels of Nlrp3 and Il1b, it is likely that CB1R can directly cause NLRP3 inflammasome activation.…”
Section: Discussionsupporting
confidence: 91%
“…S6A-E). Similar to previous reports (24,25,33), AEA-induced expression of Mcp1, Nlrp3, and Il1b were suppressed by the p38 MAPK inhibitor, SB202190 (Supplemental Fig. S6C-E).…”
Section: Increased Energy Expenditure By Aj5012 In Dio Micesupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, AJ5012 (10-20 mg/kg/day), a peripheral CB1 antagonist, was reported to cause a significant weight loss, increase energy expenditure, ameliorate glycemic control and insulin sensitivity, and to reduce inflammation in rodent model [219]. Similarly, AJ5018 (10 mg/kg/day) was shown to improve metabolic abnormalities and suppress adipose tissue inflammation via moderation of macrophage infiltration, activation of the NLRP3 inflammasome, and reducing production of pro-inflammatory cytokines in mice [220]. Neither compound elicits neurobehavioral adverse effects due to low brain penetrance.…”
Section: Obesitymentioning
confidence: 99%
“…In addition, researchers could induce activation of the NLRP3 inflammasome directly via the TLR4 signaling pathway without the need for other secondary activators [13]. NLRP3 inflammasome responds to a variety of infectious and endogenous ligands and is involved in a variety of autoimmune diseases, such as obesity [14], diabetes mellitus [15,16], arthritis [17,18], and Alzheimer's disease [19]. for life [6].…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%